Habitat Selection and Population Trends in Terrestrial Bird Species of Robinson Crusoe Island: Habitat Generalists Versus Forest Specialists - Vergara-Egert, P (2011)
Habitat loss and degradation on oceanic islands are key processes leading to population decline of endemic birds and facilitating the establishment of invasive bird species. In this study, carried out in the Robinson Crusoe Island, we assessed density and habitat selection of terrestrial bird species, including juan fernandez firecrown and juan fernandez tit-tyrant, two endemics, as well as green-backed firecrown and austral thrush, which apparently originate from the mainland. Results show that perturbed habitats contained a low density of the endemic species whereas the mainland species were significantly more abundant in perturbed scrub habitats. Bird species show different habitat selection patterns, with endemics selecting for native forest and mainland species selecting for perturbed habitats, or using them at random. Bird species experienced temporal trends in their overall population sizes, with the endemic tit-tyrant suffering a significant decline in its population size of about 63% between 1994 and 2009. Only mainland species exhibited temporal changes in habitat use, significantly reducing their densities in the preferred scrub habitats, possibly as a response to decreased habitat quality. Thrushes apparently were able to compensate the population decrease in one non native habitat type by using native forests, a habitat giving them the opportunity of preying on nests of endemic species. We conclude that endemic bird species behave as specialists whereas the mainland species must be treated as invasive generalists on Robinson Crusoe Island. © 2011 Springer Science+Business Media B.V.